How water level management affects cladoceran assemblages in lakes lateral to a reservoir - Debastiani-Júnior, José Roberto [UNESP]; Nogueira, Marcos Gomes [UNESP] (CSIRO Publishing, 2016)
This study analysed the effects of induced water level depletion for macrophyte control in a tropical reservoir on the cladoceran fauna of two differentially connected lateral lakes. One lake, Pedra Branca, is located in the right margin and has a narrow connection to the main river-reservoir channel as well as a higher proportion of submerged macrophytes. On the opposite margin is Lake Guaritá, which is shallower and has a wider connection. Samples were collected over 16 consecutive months, including periods before, during and after depletion. Both lakes showed closely related trends in depth, pH, DO, conductivity, chlorophyll, temperature, suspended matter, phosphorus, nitrogen, silicate and ammonium variation, although a wider amplitude in variation was observed in Pedra Branca. This lake also had higher cladoceran diversity and a predominance of Chydoridae, whereas Bosminidae prevailed in Guaritá. Depletion caused a reduction in richness and an increase of Bosminidae in both lakes, although this was more pronounced in Pedra Branca. The management moderately affected both lakes but continuous application of this procedure may lead to a shift in the system steady-state and a loss of diversity that could be difficult to reverse.
Keywords: Bosminidae; Chydoridae; connectivity; macrophyte control; reservoir management